Protective Regulatory T Cell Immune Response Induced by Intranasal Immunization With the Live-Attenuated Pneumococcal Vaccine SPY1 via the Transforming Growth Factor-β1-Smad2/3 Pathway - Liao, Hongyi; Peng, Xiaoqiong; Gan, Lingling; Feng, Jiafu; Gao, Yue; Yang, Shenghui; Hu, Xuexue; Zhang, Liping; Yin, Yibing; Wang, Hong; Xu, Xiuyu (Frontiers in Immunology, 2018)
Vaccine effectiveness is mainly determined by the mechanism mediating protection, emphasizing the importance of unraveling the protective mechanism for novel pneumococcal vaccine development. We previously demonstrated that the regulatory T (Treg) cell immune response has a protective effect against pneumococcal infection elicited by the live attenuated pneumococcal vaccine SPY1. However, the mechanism underlying this protective effect remains unclear. In this study, a short synthetic peptide (P17) was used to down-regulate Treg cells during immunization and subsequent challenges in a mouse model. In immunized mice, increase in immune cytokines (IL-12p70, IL-4, IL-5, and IL-17A) induced by SPY1 were further up-regulated by P17 treatment, whereas the decrease in the infection-associated inflammatory cytokine TNF-α by SPY1 was reversed. P17 also inhibited the increase in the immunosuppressive cytokine IL-10 and inflammatory mediator IL-6 in immunized mice. More severe pulmonary injuries and more dramatic inflammatory responses with worse survival in P17-treated immunized mice indicated the indispensable role of the Treg cell immune response in protection against pneumococcal infection by maintaining a balance among acquired immune responses stimulated by SPY1. Further studies revealed that the significant elevation of active TGF-β1 by SPY1 vaccination activated FOXP3, leading to increased frequencies of CD4+CD25+Foxp3+ T cells. Moreover, SPY1 vaccination elevated the levels of Smad2/3 and phosphor-Smad2/3 and down-regulated the negative regulatory factor Smad7 in a time-dependent manner during pneumococcal infection, and these changes were reversed by P17 treatment. These results illustrate that SPY1-stimulated TGF-β1 induced the generation of SPY1-specific Tregs via the Smad2/3 signaling pathway. Additionally, SPY1-specific Treg cells may participate in protection via the enhanced expression of PD-1 and CTLA-4. The data presented here extend our understanding of how the SPY1-induced acquired Treg cell immune response contributes to protection elicited by live attenuated vaccines and may be helpful for the evaluation of live vaccines and other mucosal vaccine candidates.